Multiple growth-associated nuclear proteins immunoprecipitated by antisera raised against human c-myc peptide antigens. - Persson, H (1986)
Different antisera raised against various regions of the human c-myc protein were used to identify four human c-myc proteins with apparent molecular masses in sodium dodecyl sulfate-polyacrylamide gels ranging from 64 to 68 kilodaltons (phosphoproteins pp64 and pp67 and nonphosphorylated proteins p65 and p68). pp64 and p65 were the major detectable c-myc proteins, and pp67 and p68 were minor but specific components of the immunoprecipitates. The c-myc proteins were all localized in the cell nucleus. Accumulation of [35S]methionine-labeled p65 was observed after pulse-labeling and chase, suggesting that the stable p65 c-myc protein is generated posttranslationally from short-lived precursors. pp64, pp67, and p68 possessed short half-lives and may therefore be precursors of the stable p65. Confirmation of the nuclear localization of the human c-myc proteins was obtained by immunofluorescent staining. The human c-myc proteins were revealed as a pattern of punctate nuclear staining with, particularly for p65, nucleolar enhancement that left an unstained annulus surrounding the nucleolus.